LOGISTICS MANAGEMENT AND ONLINE DISTRIBUTION SNAKESKIN GOURAMI’S PRODUCTS OF LOCAL ENTERPRISE SAMUT PRAKARN PROVINCE - rabob, chutira; Rattanaparinyanukool, Kantigamaht; Sanhapuckdee, Banjertsak; Phochanikorn, Patchara; Tharakhum , Pornvisa; Kraisamrong , Apinya; Supruang, Jariya (Business Administration and Management Journal Review, 2021)
The objectives of this research article are to analyze logistics management and online distribution snakeskin gourami’s of local enterprises in Samut Prakan province and performance improvement guideline in logistics and distribution. The sample group consisted of 90 from farmers/processors, middleman, transporters and general entrepreneur. The instruments used in the study were interview, focus group and seminar/workshop. The data were analyzed by using frequency, percentage, mean. The results of this research founded that most entrepreneur sales snakeskin gourami’s products via offline more than online 70/ 30 ratio. Transportation in Bangkok area have lower average shipping cost than upcountry which the seller earns from the different incurred. Performance improvement guidelines in snakeskin gourami logistics and distribution including the development of online selling knowledge must be done continuously, the modern entrepreneur involved, the delivery time has an impact snakeskin gourami fish quality, standard packaging design to reduce transportation cost and consumer perceive the value and benefit.